2021
DOI: 10.1590/1983-21252021v34n408rc
|View full text |Cite
|
Sign up to set email alerts
|

Seed Treatment With Trichoderma and Chemicals to Improve Physiological and Sanitary Quality of Wheat Cultivars1

Abstract: Seed treatment with fungi of the genus Trichoderma spp. provides several benefits, including plant growth promotion, stress tolerance, and pathogenic fungi control. Moreover, to avoid inadequate doses and unnecessary costs, these treatments must be applied in proper amounts. However, no study has evaluated their applicability in wheat seeds. This study aimed to determine the most efficient dose of Trichoderma-based products applied as a seed treatment for improving the physiological and sanitary quality of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
0
0
Order By: Relevance
“…The biological potency of T. viride talc-based formulation (1% w/w) was found effective against FOC (Fusarium oxysproum f.sp ciceri), which caused wilt of chickpea and also improved the physiological parameters of the crop [200]. In a study by Couto et al (2021), wheat seeds were primed with two distinct strains of Trichoderma, T. harzianum, and T. asperellum (2 × 10 12 CFU 100 kg −1 seed). Couto et al (2021) revealed that antagonist boosts the percentage of seedling emergence, root and shoot lengths, and shoot dry matter under greenhouse conditions [243].…”
Section: Seed Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The biological potency of T. viride talc-based formulation (1% w/w) was found effective against FOC (Fusarium oxysproum f.sp ciceri), which caused wilt of chickpea and also improved the physiological parameters of the crop [200]. In a study by Couto et al (2021), wheat seeds were primed with two distinct strains of Trichoderma, T. harzianum, and T. asperellum (2 × 10 12 CFU 100 kg −1 seed). Couto et al (2021) revealed that antagonist boosts the percentage of seedling emergence, root and shoot lengths, and shoot dry matter under greenhouse conditions [243].…”
Section: Seed Treatmentmentioning
confidence: 99%
“…In a study by Couto et al (2021), wheat seeds were primed with two distinct strains of Trichoderma, T. harzianum, and T. asperellum (2 × 10 12 CFU 100 kg −1 seed). Couto et al (2021) revealed that antagonist boosts the percentage of seedling emergence, root and shoot lengths, and shoot dry matter under greenhouse conditions [243]. In another study, three antagonists, namely, T. koningii, T. viride, T. asperelum, and T. reseii, were used as bio slurry for seed treatment of peanut crops.…”
Section: Seed Treatmentmentioning
confidence: 99%
“…with three (npar="LL.3"), four (npar="LL.4"), or five (npar="LL.5) log( ))Fungicide dose-response(Noel et al, 2018), Tomato brown rugose fruit virus (ToBRFV) progress in tomato cultivars(González-Concha et al, 2021) with four (npar="BC.4") or five parameters (npar="BC.5") response(Schabenberger et al, 1999), Trichoderma asperellum doses in wheat seeds(Couto et al, 2021) -Streibig with four (npar="CRS.4") or five (npar="CRS.5") parameters ) log( ))…”
mentioning
confidence: 99%